2018
DOI: 10.1377/hlthaff.2017.1688
|View full text |Cite
|
Sign up to set email alerts
|

High Spending Growth Rates For Key Diseases In 2000–14 Were Driven By Technology And Demographic Factors

Abstract: We introduce a new source of detailed data on spending by medical condition to analyze US health care spending growth in the period 2000-14. We found that thirty conditions, which represented only 11.5 percent of all conditions studied, accounted for 42 percent of the real growth rate in per capita spending during this period, even though they accounted for only 13 percent of overall spending in 2000. Primary drivers of spending growth included the use of new technologies, a shift toward the provision of preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies included the same cost components, and valuation methods differed considerably. For example, North American studies often reported insurance claims as costs, possibly leading 36,37,45,48,52,56,57,62,84,95 As most studies only reported costs and not resource use, it was not possible to determine if a difference in resource use explained cost differences or whether this was due to differing prices per resource. We aimed to reduce heterogeneity by stratifying studies based on disease and geographical area.…”
Section: Limitationsmentioning
confidence: 99%
“…24 Years later there were no savings; in fact, new technology is a primary driver of expenditure growth for many common diagnoses. 25 Technology can measure but not improve quality. 26 In many industries, technology reduces the number of human beings required to do the work.…”
Section: Technology Replaces Peoplementioning
confidence: 99%
“…We estimate the spending equation for each of the 5 multiply imputed data sets and then average the estimates. To identify the best fitting regression model, we explored several variants of Generalized Linear Models (GLM) using both one and two-part models [22][23][24][25][26][27][28][29][30][31].…”
Section: Plos Onementioning
confidence: 99%